Ultrahigh ionic conduction in water-stable close-packed metal-carbonate frameworks - Manna, Biplab; Desai, Aamod V.; Illathvalappil, Rajith; Gupta, Kriti; Sen, Arunabha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2017)
Utilization of the robust metal-carbonate backbone in a series of water-stable, anionic frameworks has been harnessed for the function of highly efficient solid-state ion conduction. The compact organization of hydrophilic guest ions facilitates water-assisted ion-conduction in all the compounds. The dense packing of the compounds imparts high ion-conducting ability and minimizes the possibility of fuel crossover, making this approach promising for design and development of compounds as potential components of energy devices. This work presents the first report of evaluating ion-conduction in a purely metal-carbonate framework, which exhibits high ion-conductivity on the order of 10(-2) S cm(-1) along with very low activation energy, which is comparable to highly conducting well-known crystalline coordination polymers or commercialized organic polymers like Nafion.